(untitled) (CaJoST, 2024)
Securidaca longipedunculata is a shrub of the family Polygalaceae. It is a potent medicinal plant used in management of microbial infection others. The aim of this study is to characterize, and evaluate the antimicrobial activity of sorbitan isolated from the leaves of Securidaca Longipedunculata (Fresen). The methanol extract of S. longipedunculata was subjected to chromatographic purification, which led to isolation of compound identified as sorbitan by analysis of the 1D and 2D-NMR spectral data. The antimicrobial screening against bacterial pathogens (Methicillin-resistant staphylococcus aureus (MRSA), Vancomycin-resistant enterococci (VRE) S. aureus, S. feacalis, E. coli, S. typhimurium, P. fluorescens, K. pneumoniea) and fungal pathogens (C. albicans, C. krusei, A. niger, A. fumigates, and Microsporumcanis) was performed using agar well diffusion and broth dilution method. In-vitro inhibition of these pathogenic microorganisms produced inhibition zone ranging from 25 - 32 mm for sorbitan; the standard drugs sparfloxacin and ciprofloxacin (500µg/mL) had zone of inhibition ranging from 28 - 40 mm. While the antifungal drugs fluconazole and Fulcin exhibited zone of inhibition ranging from 27 mm to 34 mm. Minimum inhibition concentration (MIC) values of sorbitan ranged from 25 - 12.5 mg/mL. The minimum bactericidal concentration (MBC)/minimum fungicidal concentration (MFC) of sorbitan was observed to be 50 - 25 mg/mL. Sorbitan was isolated and characterized from S. longipedunculata leaves extract and it demonstrated good antimicrobial activity which validates the used of the plant leaves in the treatment of microbial infections in traditional medicine